(untitled) (Biological Sciences - PJSIR, 2003)
Different feed ingredients i.e. wheat, sorghum, maize, corn gluten meal, rice bran, cotton seed meal, mustard seed meal, sunflower meal, soy bean meal, sesame meal, peanut meal and broiler feeds were procured from local market and analyzed for chemical composition and toxic factors. The oilseed cakes and rice bran meal were treated to eliminate the toxic factors. Detoxification of feed ingredients resulted in decrease in gossypol from 0.31 to 0.05% in cotton seed meal, allylisothiocyanate from 1.55 to traces in mustard seed meal, chlorogenic acid from 3.20 to 0.95% in sunflower meal and trypsin inhibitor from 72.10 to 17.20 mg/g in soy bean meal. Phytic acid contents in oilseed cakes i.e. cotton seed, mustard seed, sunflower, soybean, and rice bran meals before and after treatments were reduced from 2.91 to 0.43, 3.54 to 0.40, 2.84 to 0.52, 3.22 to 0.64 and 2.60 to 0.42%, respectively.